The Application of Cucumber Juice Administration in Hypertensive Patients (Literature Review) - Ranti, Galuh Mega; Marisa, Dewi Erna (INDOGENIUS, 2025)
Background & Objective: Hypertension is a condition in which a person experiences an increase in blood pressure above normal limits, which can cause pain or death. Efforts to lower blood pressure can be done through pharmacological and non-pharmacological treatments. For people with hypertension, non-pharmacological therapy is an alternative. This involves consuming foods such as cucumbers, which are high in potassium, calcium, and other important nutrients. Method: The research method used a literature review of studies published between 2020 and 2024. The literature search employed a data strategy using the keywords “hypertension” and “cucumber,” utilizing the Google Scholar and PubMed databases. The criteria included articles discussing the relationship between hypertension and cucumber, with full-text availability. Result: The results from 10 articles indicate that consuming cucumber juice in hypertensive patients is effective in lowering blood pressure. Conclusion: It is recommended that hypertensive patients consume cucumber juice regularly to achieve effective results; however, hypertensive patients should also maintain a balanced diet and engage in sufficient physical activity.